Dominasi dan ketidakadilan negara dan korporasi dalam kasus bencana lumpur Lapindo - Oman Sukmana (Faculty of Social and Political Science, Universitas Airlangga, 2017)
The domination of the state (government) and Corporate (PT LBI) in the oil and gas resource management lead Lapindo mudflow disaster that caused misery to the people. This study aims to assess the forms of domination and injustice by the state (government) and the corporation in the case of Lapindo mudflow disaster, and how Lapindo mudflow disaster victims negotiate (resist) against the state (government) and corporations in an effort to fight for their rights. This study used a qualitative approach with case study. Subjects and informantsresearch include: (1) Lapindo mudflow disaster victims; (2) group coordinator of Lapindo mudflow disaster victims; (3) Public figures Siring village, Tanggulangin, Renokenongo, Jabon, and Jatirejo, Porong district, Sidoarjo; (4) Representation of the corporation (PT. LBI); and (5) Representation of BPLS. The data collection process using the in-deepth interviews, observation, focus group discussions, and review documents. Stage processing and data analysis includes the coding process, memoing, and concept mapping. The results showed that the government (the state) and the corporation (PT LBI) action dominating the oil and gas resource management in the area of Porong district, Sidoarjo regency, East Java, resulting misery for the victims (people). Forms of injustice felt by residents Lapindo mudflow disaster victims not only related to the issue of compensation for land and building assets alone, but more than that, including various dimensions. Through a variety of collective action, such as demonstrations and negotiations, Lapindo mudflow disaster victims filed various charges, such as demands for payment of compensation for land and building assets destroyed.